2013
DOI: 10.1007/s11102-013-0543-8
|View full text |Cite
|
Sign up to set email alerts
|

Adamantinomatous craniopharyngiomas express tumor stem cell markers in cells with activated Wnt signaling: further evidence for the existence of a tumor stem cell niche?

Abstract: Our results indicate tumor stem cell-like characteristics of β-catenin accumulating cell clusters in adaCP, which may represent a tumor stem cell niche and might contribute to tumor recurrence. The potential impact of these special cell groups in regard to future CP management, including postoperative follow-up and additional treatment remains to be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 50 publications
2
37
1
Order By: Relevance
“…3,4,15 This, coupled with their stem cell-like markers, e.g., CD44, SOX2, have made these clusters of particular interest when studying the signaling pathways underlying the development and progression of ACP. 4,24 Indeed activation of CTNNB1 in adult pituitary SOX2-positive stem cells alone leads to tumors resembling ACP. 4 Studies have shown that these clusters may act as signaling centers expressing high levels of secreted factors such as SHH, FGFs, BMPs and WNTs, with paracrine actions on neighboring cells.…”
Section: Molecular Biology Of B-cateninaccumulating Cell Clustersmentioning
confidence: 99%
“…3,4,15 This, coupled with their stem cell-like markers, e.g., CD44, SOX2, have made these clusters of particular interest when studying the signaling pathways underlying the development and progression of ACP. 4,24 Indeed activation of CTNNB1 in adult pituitary SOX2-positive stem cells alone leads to tumors resembling ACP. 4 Studies have shown that these clusters may act as signaling centers expressing high levels of secreted factors such as SHH, FGFs, BMPs and WNTs, with paracrine actions on neighboring cells.…”
Section: Molecular Biology Of B-cateninaccumulating Cell Clustersmentioning
confidence: 99%
“…9,11,12,24,28,38 As a result of this mechanism, nuclear accumulation of b-catenin is a histological hallmark of CTNNB1 mutation. 10,12,16,26,41 In the case of craniopharyngiomas, mutation of CTNNB1 has been described in 69%-100% 9,20,28 of ACP specimens, while it is not routinely observed in PCP or other parasellar tumors. 9,28 In the most detailed study to date, CTNNB1 mutation was identified in 95% of ACP specimens, using massively parallel sequencing and targeted genotyping.…”
Section: Ctnnb1 Mutationmentioning
confidence: 99%
“…26 As with therapies directed at the SHH pathway, those targeting the EGF pathway require further clarification through preclinical study before they could enter clinical use and impact neurosurgical care.…”
mentioning
confidence: 99%
“…The stem cell markers SOX2 [16] , POU1F5/OCT4 [16], SOX9 [16,17], and CD44 [18] have previously been described in association with ACP. In this study, we aimed to increase current knowledge regarding the expression patterns of pituitary stem cell markers in ACP and pituitary adenomas, including the markers DLL4, NANOG, NOTCH2, and POU1F5/OCT4, to better understand the tumour development and recurrence process.…”
Section: Introductionmentioning
confidence: 99%